The Common Sports Injuries among the Female Students in the Directorate of Education in Al-Karak Governorate in the South of Jordan - Prof. Dunya Mahmoud Al-Asasfeh (Zien Journals, 2022)
This study aimed at identifying the most common types of sports injuries among the female students in the directorate of education in Al-Karak governorate in the South of Jordan and the most common sites exposed to sports injuries as well as the most common causes leading to sports injuries among the study sample individuals. The study used the descriptive approach with its survey image to collect data, and the questionnaire was used as the study instrument for data collection. The study sample consisted of (201) female students, who were chosen using the intentional method. The researcher used (SPSS) for data analysis. The results revealed that the most common types of sports injuries among the female students were muscle bruises and the most common causes leading to sports injuries are the insuitability of the pitch ground and the most common anatomical sites exposed to sports injuries are the groin area. The results revealed that there are differences between the female students in the public and private schools in favor of the public schools. Based on the results, the study recommended the necessity of providing sufficient area of pitches and other sports facilities inside schools to introduce the lesson of physical education in the appropriate way.
Keywords: sports injuries; female school students; directorate of education; Al-Karak; Jordan